2019
DOI: 10.1038/s41598-019-56622-5
|View full text |Cite|
|
Sign up to set email alerts
|

Dichotomic effects of clinically used drugs on tumor growth, bone remodeling and pain management

Abstract: Improvements in the survival of breast cancer patients have led to the emergence of bone health and pain management as key aspects of patient’s quality of life. Here, we used a female rat MRMT-1 model of breast cancer-induced bone pain to compare the effects of three drugs used clinically morphine, nabilone and zoledronate on tumor progression, bone remodeling and pain relief. We found that chronic morphine reduced the mechanical hypersensitivity induced by the proliferation of the luminal B aggressive breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…The ipsilateral femurs were removed and postfixed for 48 h in the same solution and then washed in PBS for ex vivo µCT experiments. Scans were performed at the McGill Bone Center using a high-resolution desktop micro-CT scanner, as previously described 61 . Rat femurs were scanned at an X-ray source power of 45 keV/222 µA and at a resolution of 11.25 µm/pixel.…”
Section: Methodsmentioning
confidence: 99%
“…The ipsilateral femurs were removed and postfixed for 48 h in the same solution and then washed in PBS for ex vivo µCT experiments. Scans were performed at the McGill Bone Center using a high-resolution desktop micro-CT scanner, as previously described 61 . Rat femurs were scanned at an X-ray source power of 45 keV/222 µA and at a resolution of 11.25 µm/pixel.…”
Section: Methodsmentioning
confidence: 99%
“…Ipsilateral femurs were removed and post-fixated 48 h in the same solution then washed in PBS for ex vivo µCT experiment. Scans were performed at the McGill Bone Center using a high-resolution desktop Micro-CT scanner, as previously described 65 . Rat femurs were scanned at X-ray source power of 45 keV/222 µA and at a resolution of 11.25 µm/pixel.…”
Section: Ex Vivo µCtmentioning
confidence: 99%
“…The anti-tumor effects of opioids are controversial [21], though some studies have reported the ability of opioids to decrease tumor growth. For instance, morphine treatment was found capable of suppressing lung cancer cell proliferation [22], while no effect was seen in breast tumor growth [23], suggesting that morphine treatment may be beneficial in a cancer type-specific manner.…”
Section: Analgesicsmentioning
confidence: 99%
“…The analgesics metamizole and paracetamol have been shown to inhibit pancreatic cancer growth [29] while metamizole and acetaminophen exert cytotoxic effects in colon cancer [30]. Synthetic cannabinoids such as nabilone and cannabidiol also show promise as cancer therapeutics [23], yet this remains controversial [31,32].…”
Section: Analgesicsmentioning
confidence: 99%